Association between anthropometric indices and hypertension: identifying optimal cutoff points for U.S. adults across different populations - Zhang, Xueliang; Nie, Yan; Li, Dan; Zhou, Chunhua (Frontiers in Pharmacology, 2024)
ObjectiveThis study compares the relationships between five anthropometric indices, a body shape index (ABSI), body roundness index (BRI), waist circumference (WC), body mass index (BMI) and waist-to-height ratio (WHtR), and hypertension, assessing their predictive capacities. The aim is to determine the specific numerical changes in hypertension incidence, systolic blood pressure (SBP) and diastolic blood pressure (DBP) for each increase in standard deviation of these indices, and to identify the optimal predictive indicators for different populations, including the calculation of cutoff values.MethodsThis study used data from the NHANES datasets spanning 2007 to 2018. Logistic regression analysis was used to quantify the associations between these anthropometric indices and hypertension, calculating β coefficients and odds ratios (ORs). Receiver operating characteristic (ROC) analysis was used to evaluate the predictive ability of each index for hypertension.ResultsFor each increase in standard deviation in WC, BMI, WHtR, ABSI and BRI, the prevalence of hypertension increased by 33% (95% CI: 27%–40%), 32% (95% CI: 26%–38%), 35% (95% CI: 28%–42%), 9% (95% CI: 4%–16%) and 32% (95% CI: 26%–38%), respectively. The SBP correspondingly increased by 2.36 mmHg (95% CI: 2.16–2.56), 2.41 mmHg (95% CI: 2.21–2.60), 2.48 mmHg (95% CI: 2.28–2.68), 0.42 mmHg (95% CI: 0.19–0.66) and 2.46 mmHg (95% CI: 2.26–2.66), respectively. Similarly, DBP increased by 1.83 mmHg (95% CI: 1.68–1.98), 1.72 mmHg (95% CI: 1.58–1.87), 1.72 mmHg (95% CI: 1.57–1.88), 0.44 mmHg (95% CI: 0.27–0.62) and 1.64 mmHg (95% CI: 1.48–1.79). In the youth and middle-aged groups, WC had the best predictive ability, with AUCs of 0.749 and 0.603, respectively. Among the elderly group, the AUCs for all five indices ranged between 0.5 and 0.52.ConclusionIncreases in WC, BMI, WHtR and BRI are significantly associated with higher incidences of hypertension and increases in SBP and DBP, while the impact of ABSI on blood pressure is relatively weak. Stratified analysis indicates significant age-related differences in the predictive value of these indices, with the strongest associations observed in the youth group, followed by the middle age group, and the weakest in the elderly. WC demonstrates excellent predictive ability across youth populations.